Early clinical and radiological course, management, and outcome of intracerebral hemorrhage related to new oral anticoagulants - Purrucker, Jan; Rizos, Timolaos; Khan, Shujah; Wolf, Marcel; Hennerici, Michael G.; Steiner, Thorsten (JAMA neurology, 2016)
Importance: Intracerebral hemorrhage (ICH) is the most devastating adverse event in patients receiving oral anticoagulation. There is only sparse evidence regarding ICH related to the use of non–vitamin K antagonist oral anticoagulant (NOAC) agents. Objective: To evaluate the early clinical and radiological course, acute management, and outcome of ICH related to NOAC use. Design, Setting, and Participants: Prospective investigator-initiated, multicenter observational study. All diagnostic and treatment decisions, including administration of hemostatic factors (eg, prothrombin complex concentrate), were left to the discretion of the treating physicians. The setting was 38 stroke units across Germany (February 1, 2012, to December 31, 2014). The study included 61 consecutive patients with nontraumatic NOAC-associated ICH, of whom 45 (74%) qualified for the hematoma expansion analysis. Main Outcomes and Measures: Hematoma expansion, intraventricular hemorrhage, and reversal of anticoagulation during the acute phase. Recorded were the 3-month functional outcome, factors associated with an unfavorable outcome (modified Rankin Scale score, 3-6), any new intraventricular extension or an increase in the modified Graeb score by at least 2 points, and the frequency of substantial hematoma expansion (defined as relative [≥33%] or absolute [≥6-mL] volume increase). Results: In total, 41% (25 of 61) of patients with NOAC-associated ICH were female, and the mean (SD) patient age was 76.1 (11.6) years. At admission, the median National Institutes of Health Stroke Scale score was 10 (interquartile range, 4-18). The mean (SD) baseline hematoma volume was 23.7 (31.3) mL. In patients with sequential imaging for the hematoma expansion analysis, substantial hematoma expansion occurred in 38% (17 of 45). New or increased intraventricular hemorrhage was observed in 18% (8 of 45). Overall mortality was 28% (17 of 60 [follow-up data were missing in 1 patient]) at 3 months, and 65% (28 of 43) of survivors had an unfavorable outcome (modified Rankin Scale score, 3-6). Overall, 57% (35 of 61) of the patients received prothrombin complex concentrate, with no statistically significant effect on the frequency of substantial hematoma expansion (43% [12 of 28] for prothrombin complex concentrate vs 29% [5 of 17] for no prothrombin complex concentrate, P = .53), or on the occurrence of an unfavorable outcome (modified Rankin Scale score, 3-6) (odds ratio, 1.20; 95% CI, 0.37-3.87; P = .76). Conclusions and Relevance: Non–vitamin K antagonist oral anticoagulant–associated ICH has a high mortality and an unfavorable outcome, and hematoma expansion is frequent. Larger-scale prospective studies are needed to determine whether the early administration of specific antidotes can improve the poor prognosis of NOAC-associated ICH.